2011
DOI: 10.1891/0886-6708.26.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Routine Inequality: Violent Victimization at the Intersection of Race and Ethnicity Among Females

Abstract: Criminological research has clearly demonstrated that the risk of violent victimization varies across gender. More complex are the differences across race and ethnicity within gender groups. Past studies have established that victimization rates among Black females exceed those of White and Latina females. Although this pattern has been established, the reason for these differences between females must continue to be explored. We draw on situational and contextual features of routine activities and lifestyle t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…A number of studies have applied criminal opportunity theories to study the predictors of victimization differences by race and ethnicity (Like-Haislip & Warren, 2011; Peguero, 2013; Peguero, Popp, & Koo, 2015; Peguero et al, 2013). According to these theories, victimization is a function of everyday activities and lifestyles that place individuals in situations where criminal opportunities are enhanced (Cohen & Felson, 1979; Cohen, Kluegel, & Land, 1981; Hindelang, Gottfredson, & Garofalo, 1978).…”
mentioning
confidence: 99%
“…A number of studies have applied criminal opportunity theories to study the predictors of victimization differences by race and ethnicity (Like-Haislip & Warren, 2011; Peguero, 2013; Peguero, Popp, & Koo, 2015; Peguero et al, 2013). According to these theories, victimization is a function of everyday activities and lifestyles that place individuals in situations where criminal opportunities are enhanced (Cohen & Felson, 1979; Cohen, Kluegel, & Land, 1981; Hindelang, Gottfredson, & Garofalo, 1978).…”
mentioning
confidence: 99%
“…An additional limitation to the study is a lack of inclusion of valid measures of race and ethnicity that are likely reflective of both international and non-international students. This omission is important as past research has found that racial and ethnic minorities in the United States are at heightened risk of violent victimization (Hart, 2003;Lauritsen & Heimer, 2009;Like-Haislip & Warren, 2011). Unfortunately, the data available for the current study contained only a U.S.-based measure of race that is a self-report, and it did not contain a separate measure of ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study did not assess the variables predictive of victimization, prior work has suggested that certain situational and daily routines increase the odds of victimization for Hispanics. For example, Like-Haislip and Warren (2011) applied a routine activities approach and found Latina and White women who spent time shopping outside the home had a greater risk of victimization. This study also indicated that minority females who utilized public transportation have a greater risk of violent victimization compared with White females.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most robust findings in the criminological literature is the unequal distribution of crime and victimization across race and ethnicity (Walker, Spohn, & DeLone, 1996). Differences in risk of victimization across races and ethnicities have been evident in self-report studies and official data for decades (Catalano, 2006; Like-Haislip & Warren, 2011; Rennison, 2002). Overall, prior research suggests that racial and ethnic minorities, especially Blacks, are more likely to be victimized relative to Whites.…”
Section: Introductionmentioning
confidence: 99%